2008
DOI: 10.1007/s00534-007-1292-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vessel sealing system for major Glisson bundles and major bile ducts

Abstract: The VSS is useful for the safe sealing of not only the major Glisson bundles but also the major bile ducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…A VSS has been reported to be an effective and safe tool that reduces the time needed to perform a liver resection . We have previously reported that a VSS is useful for the safe sealing of major Glisson's capsules and major bile ducts . We confirmed Gllison's capsules with diameter of 13.8 mm could be sealed and completely fused together histologically in a pig model.…”
Section: Discussionsupporting
confidence: 59%
“…A VSS has been reported to be an effective and safe tool that reduces the time needed to perform a liver resection . We have previously reported that a VSS is useful for the safe sealing of major Glisson's capsules and major bile ducts . We confirmed Gllison's capsules with diameter of 13.8 mm could be sealed and completely fused together histologically in a pig model.…”
Section: Discussionsupporting
confidence: 59%
“…[1][2][3][4][5][6][7][8] A bipolar electrosurgical device reportedly achieves hemostasis of the ovarian pedicle during laparoscopic-assisted ovariohysterectomy. 9 It can safely seal blood vessels with diameters as large as 7 mm.…”
mentioning
confidence: 99%
“…11,12 However the LigaSure system has not previously been reported for sealing of the cystic duct in human studies, but in an animal study we found the method to be safe. 8 This has recently been confirmed by a study from Nii et al 13 of closure of the major bile duct in pigs. One potential advantage of the LigaSure is that it leaves no metallic objects in the body and that the risk of damage of the surrounding structures is minimal due to the bipolar cautery.…”
Section: Discussionmentioning
confidence: 71%